Effect of dynamic marketing capabilities in strategic direction (A survey of a number of private banks / Baghdad) - حسن, آمال منصور (Journal of Economics and Administrative Sciences, 2020)
The intensification of competition in the business environment has forced research organizations to develop marketing dynamics that help them to sense and conceptualize market opportunities and uncertainties. Then, the marketing capabilities of the organization are restructured and developed according to mechanisms such as speed, timing, and frequency of application. The problem of most organizations is their lack of interest in capabilities  Marketing dynamics, which represent the most important factor in enhancing their marketing performance, so the objective of the research is to identify the most important capabilities that banks should pay attention to and evaluate their role in determining the strategic direction of these banks, and test the hypotheses of correlation and influence  The variables of the study were distributed through a sample of 62 managers, heads of departments and divisions working in a group of private banks (Ceyhan Bank, Northern Bank, Iraqi Commercial Banks). These hypotheses were tested using a variety of statistical means the most important conclusions of the study are the interest of the banks in the research sample by investing in the dynamic marketing capabilities of (customer relationship management, marketing knowledge, service development) because they are important in enhancing the ability of the senior management in determining the  Strategic DBS to ensure growth within the circle of competition and maintain market share, it has recommended research sample need to research and attention Balmekdrat dynamic marketing as banks and contribute actively in defining strategic direction.